Lichnostnaja samoreguljacija v sistemepsihologicheskoj podgotovlennosti sportsmenovvysokoj kvalifikacii v parusnom sporte - Voronova, V.; Rodina, Y. (Science in Olympic Sport, 2018)
Objective. To develop, theoretically substantiate and experimentally test the program for improving the psychological pre-paredness of elite yachtsmen on the basis of personal self-regulation techniques. Methods: theoretical analysis of specialized literature and best practices; analysis of documentary materials; pedagogical methods; methods of psychological diagnosis; Korotkov`s gasdischarge visualization method; methods of mathematical statistics. Results. Techniques of self-regulation become particularly important for psychological preparation of elite yachtsmen. The study of the level of psychological preparedness of yachtsmen of the national Olympic team in sailing showed the problematic parameters, which stipulate the need for further work on the psychological preparation of athletes. It was found that the psychological preparedness of yachtsmen of the Ukrainian national team is low in terms of self-management of competitive activity. The paper presents the results of application of the developed program of personal self-regulation for yachtsmen, which con-sists of six stages: the diagnostic; the developing; the regulatory; the diagnostic-regulatory; the correctional; and the reflexive. The program was used in the annual cycle of training of elite yachtsmen. Particular attention was paid to the mental training, which included elements selected according to the specifi cs of yachtsmen's competitive exercises.It was shown that the personality of an elite yachtsman plays a large role in mobilizing the state of competitive readiness andactivating the mode of conscious control over own actions during the competition. Conclusion. A current view of the process of psychological preparation of elite athletes includes the addressing of the issues of a holistic approach to the psychological support for the athlete along with mobilization of his unused capabilities and not just the avoidance of unfavorable factors in the competitive period. Implementation of this approach is facilitated by the development of certain psychological qualities of the athlete's personality, his awareness of his mental states in difficult conditions of sporting activity, as well as mastering the techniques of psychological regulation.